Moving towards universal health coverage : challenges for the present and future in China - Luk, Sabrina Ching Yuen (IGI Global, 2020)
This study uses a refined version of historical institutionalism to critically examine the complex interplay of forces that shape the health insurance reform trajectory in China since the mid-1980s and identifies problems that impede the government from achieving universal health coverage (UHC). It shows that China's multi-layered social health insurance system has covered more than 95 percent of its population, but failed to provide insured people with access to a range of essential services and make health care affordable. To achieve UHC, the government has to overcome significant hurdles, which include the inherently discriminatory design of the social health insurance system, disorder in the drug distribution system, deficits in the funding of health insurance, and insufficient medical protection for the old people.